2020
DOI: 10.7717/peerj.9481
|View full text |Cite
|
Sign up to set email alerts
|

Association between individual retinal layer thickness and visual acuity in patients with epiretinal membrane: a pilot study

Abstract: Purpose We investigated the correlation between visual acuity (VA) and individual retinal layer thickness in the foveal, parafoveal, and perifoveal regions of patients with an idiopathic epiretinal membrane (ERM). Methods One hundred and five subjects presenting with unilateral idiopathic ERM were included in this study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In that sense, morphological changes in the inner retina may be a useful indicator of the severity of traction force. Notably, the INL thickness was also reported as an indicator of VA in the eyes with ERM [15]. Kim et al reported that the INL thickness was correlated with the degree of metamorphopsia and VA in the same eyes [5].…”
Section: Discussionmentioning
confidence: 98%
“…In that sense, morphological changes in the inner retina may be a useful indicator of the severity of traction force. Notably, the INL thickness was also reported as an indicator of VA in the eyes with ERM [15]. Kim et al reported that the INL thickness was correlated with the degree of metamorphopsia and VA in the same eyes [5].…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have reported relationship between retinal microstructure and functional visual outcome (such as visual acuity and degree of metamorphopsia) in ERM patients 11 , 13 , 20 , 21 . Especially, structural deformity in INL is known to be significantly related to visual acuity and degree of metamorphopsia 20 , 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported relationship between retinal microstructure and functional visual outcome (such as visual acuity and degree of metamorphopsia) in ERM patients 11 , 13 , 20 , 21 . Especially, structural deformity in INL is known to be significantly related to visual acuity and degree of metamorphopsia 20 , 21 . Zou et al 21 revealed that preoperative INL thickness in foveal, parafoveal, and perifoveal region correlates with postoperative improvement of visual acuity in 35 ERM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the study by Zou et al has shown, those with SD-OCT (Cirrus; Carl Zeiss Meditec Inc. ® , Dublin, CA, USA) machine-measured foveal IPL, INL, and ONL thickness at ERM 42.25 ± 13.22, 75.56 ± 28.49, and 130.9 ± 22.65 μ m, CFT was 504.93 ± 118.14 μ m [ 22 ]. There was a clear difference between the fovea layers as measured mechanically in the study and manually by us in the ERM both in absolute numbers and in the ratio of the thickness of the individual fovea layers to the CFT.…”
Section: Discussionmentioning
confidence: 99%